Reference intervals for selected haematological and clinical biochemistry measurands in Temminck’s ground pangolin (Smutsia temminckii) - Meyer, Leith Carl Rodney (University of Pretoria, 2024)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2019.